Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1515/pjvs-2015-0105
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and immunological responses of young turkeys to vaccination against Ornithobacterium rhinotraheale and different levels of dietary methionine

Abstract: The objective of this study was to verify the hypothesis that increasing levels of dietary methionine can stimulate the mechanisms of cell-mediated and humoral immunity in young turkeys. The blood and organs involved in cell-mediated and humoral immune responses were analyzed in 8-week-old turkeys that had been vaccinated against Ornithobacterium rhinotraheale (ORT) infection (on days 17 and 48). The birds were fed diets with a low (LM), medium (MM) and high (HM) methionine content (0.45 and 0.40%, 0.60 and 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 18 publications
(32 reference statements)
3
11
1
Order By: Relevance
“…In our study, similarly to earlier experiments with chickens (Deng et al, 2007;Rubin et al, 2007;Bouyeh, 2012) and turkeys (Kubińska et al, 2015b), the diet containing no supplemental DL-Met contributed to a decrease in BWG, in comparison with birds fed diets supplemented with Met at levels being in line with NRC (1994) recommendations. Dietary Met concentrations higher than the levels recommended by NRC (1994) and B.U.T.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In our study, similarly to earlier experiments with chickens (Deng et al, 2007;Rubin et al, 2007;Bouyeh, 2012) and turkeys (Kubińska et al, 2015b), the diet containing no supplemental DL-Met contributed to a decrease in BWG, in comparison with birds fed diets supplemented with Met at levels being in line with NRC (1994) recommendations. Dietary Met concentrations higher than the levels recommended by NRC (1994) and B.U.T.…”
Section: Discussionsupporting
confidence: 86%
“…Similarly to experiments with chickens (Rubin et al, 2007;Bouyeh, 2012), the diet without DL-Met deteriorated feed conversion, but only in the first month of feeding. In the previous experiments with turkeys, diets without DL-Met supplementation had no adverse effect on the growth performance of four-week-old birds , but they decreased the BWG of eight-week-old birds (Kubińska et al, 2015b).…”
Section: Discussionmentioning
confidence: 73%
“…The results of flow cytometry analysis of spleen and blood mononuclear cells provided in our study are similar to the findings reported by Kubińska et al. (2014) .…”
Section: Resultssupporting
confidence: 91%
“…This is expected to alleviate negative outcomes of HEV and improve the birds health status and resultantly (by decreasing amounts of antibiotics used) to improve turkey production effectiveness and quality of poultry products. The substances with proved, positive impact on the immune system of poultry and their body weight gains include, i.a., vitamins, probiotics, essential oils, herbs, nucleotides, and amino acids [4, 18, 19].…”
Section: Introductionmentioning
confidence: 99%